Open Source Based M-Learning Application for Supporting Distance Learning - Arief Hidayat; Victor Gayuh Utomo (Universitas Ahmad Dahlan, 2014)
The concept of learning anywhere and anytime is unable to be fully implemented because user need to find comfortable place, which is required, to follow the study. User is unable to access learning material in a way that practical, easy to use and easy to access. Based on that fact, system or application for mobile device such as hand phone, PDA or smart phone is needed.The m-learning application is developed by Computer-Based System Engineering Method based on the principal of software engineering using development steps of System Development Life Cycle (SDLC). SDLC consists of the following steps, analysis, design, implementation, testing and evaluation. Trials as alpha-test, carried out to determine operability of m-learning system on handheld devices. Trial is taken by creating trial class followed by 25 students to receive feedback about the m-learning system. Feedback result shows almost 90% of respondents consider the m-learning system is easy to use.